PENGARUH INFORMASI AKUNTANSI TERHADAP HARGA SAHAM PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN DI BURSA EFEK INDONESIA - Andriani Kusuma; Runik Puji Rahayu; Muslimatul Aina; Rika Syahadatina (Fakultas Ekonomi, Program Studi Akuntansi, 2022)
The purpose of this study was to determine the effect of accounting information on stock prices of food and beverage sub-sector manufacturing companies on the Indonesia Stock Exchange Transportation Companies Listed on the Indonesia Stock ExchangeThis research is located at the IDX Makassar (Indonesia Stock Exchange) office. The sample selection method in this research is purposive sampling method with a total sample of 5 companies. The data collection techniques collect data on the company's financial statements during the study period. The data analysis method used is multiple regression with the help of SPSS software for windows 25.00. The results showed that 1) Based on the results of data analysis, the coefficient value of ROA, ROE, NPM, and EBIT showed the effect on stock prices simultaneously. 2) Based on the results of data analysis of ROA, ROE, NPM partially significant effect on stock prices, while EBIT has no influence on the stock prices of manufacturing companies in the food and beverage sub-sector on the IDX. 3) The most dominant variable influencing ROA, ROE, NPM and EBIT on the share prices of food and beverage sub-sector manufacturing companies on the IDX is the ROA variable.